#TITLE_ALTERNATIVE# - JANUARI WAHYUDI (NIM 12304030), EKO
In order to monitor ground water movement at Semarang, seven times gravity surveys have been applied since July 2002 until November 2005. From those observed data, we can identify 4D microgravity anomaly that involve tidal correction, drift correction, and subsidence correction. For interpretation of direction ground water flow based on density contrast value, 3D inversion model of 4D microgravity anomaly that supported by geology data to accommodate the location ground water density change with depth of aquifer layers has been done. In this study, inverse modeling use GRAV3D software and the interpretation of direction ground water flow use Golden Surfer software. Using differential equation approximation (directional derivatives) on density contrast data achieved from inversion modeling, the direction of ground water flow interpreted towards the location that have density value relatively more negative or more positive to the others. Negative value of density contrast response of mass decrease relates to ground water consumption area, while the positive anomaly response of mass increase relates to ground water recharge area.